Agricultural Knowledge Grid Construction - Tan Cuiping; Zheng Huaiguo; Zhang Junfeng; Sun Sufen; Li Guangda (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In order to eliminate the ambiguity in semantic understandings during the retrieval of the users, as well as mining the relationship between the concept of agricultural knowledge, the association of knowledge among heterogeneous databases needs to be set up, which enable users to discover useful knowledge clues, and gradually form solution for the ultimate question. Based on the characteristics of agricultural knowledge and the achievements of knowledge grid research, with a combination of traditional agricultural thesauri and ontology technology, the agricultural knowledge grid was constructed with the resource layer, semantic layer and user level. It has been applied for semantic extension on retrieval, knowledge links, and knowledge reasoning diagnosis. It gains some achievements, which provide technical support and experience for the deeply agricultural knowledge services. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3272